Attribute-based multiuser authentication scheme between IoT devices for 5G environment - Su Jeong, Yoon; Tae Kim, Yong; Cheol Park, Gil (International Journal of Engineering and Technology, 2018)
Background/Objectives: Due to the development of mobile communication technology, infrastructure construction from 4G to 5G service, which is currently being serviced, is actively under way. In particular, as the types and functions of mobile phones and IoT devices using 5G services are diversified, mutual authentication technology among multiple users is required.Methods/Statistical analysis: In this paper, we propose a multi - user authentication scheme which can efficiently mutually authenticate different types of mobile phones and IoT devices that are provided with 5G service. The proposed method minimizes the authentication delay time because it identifies the authentication security parameter Î´ of multiple users requesting authentication to the server as a polynomial coefficient. As a result of the performance evaluation, the proposed method showed an average improvement of 9.3% in authentication processing time and 5.5% lower overhead than the existing method. In addition, the multiuser authentication latency was improved by 6.1% on average compared with the existing scheme.Findings: The proposed scheme minimizes the user 's authentication delay time by constructing the users who simultaneously request the 5G service into a subnet and then applying the authentication security parameter Î´ constituting each subnet to n - bit and applying it to the polynomial coefficients. Especially, for multi - user authentication, the proposed scheme divides the authentication path into two paths (main path and secondary path) to guarantee user authentication and integrity. The proposed scheme is suitable for mobile phones and IoT devices that use low power because it generates keys without performing additional cryptographic algorithms like conventional techniques when performing multi - user authentication.Improvements/Applications: In future research, we plan to apply the proposed method to the actual environment based on the results of this study.Â Â